2019
DOI: 10.11606/issn.1982-6486.rco.2019.145151
|View full text |Cite
|
Sign up to set email alerts
|

Os Tribunais de Contas na interpretação da Lei de Responsabilidade Fiscal

Abstract: O trabalho analisa as interpretações dadas à Lei de Responsabilidade Fiscal nos 19 anos de sua implantação. Como uma instituição que procura regular a gestão fiscal de governos por todo o País, parte significativa da coerção da Lei no nível regional e local cabe aos Tribunais de Contas de Estados e Municípios. Adotou-se o modelo teórico de mudança institucional de Mahoney e Thelen (2009), com evidências coletadas por questionário, para dar uma primeira explicação para a mudança incremental na legislação fiscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 3 publications
2
11
0
17
Order By: Relevance
“…One of such fragilities would be the absence of council members at full bench sessions who are selected by exams. Nunes et al (2019) demonstrate that the lack of symmetry in the compliance with the LRF arise from an interpretation Courts of Account have over some of the stone concepts, especially as to how the RCL and expense with personnel should be assessed. For the authors, those different interpretations would be related to a criterion for political indication for the council-member position, in which case many of those appointed are former representatives who have no interest in imposing penalties against leaders in the Legislative Branch or inducing budget cuts in the expenses with personnel in such branches.…”
Section: Figure 3 Limits Of the Expense With Personnel In 2018mentioning
confidence: 95%
See 1 more Smart Citation
“…One of such fragilities would be the absence of council members at full bench sessions who are selected by exams. Nunes et al (2019) demonstrate that the lack of symmetry in the compliance with the LRF arise from an interpretation Courts of Account have over some of the stone concepts, especially as to how the RCL and expense with personnel should be assessed. For the authors, those different interpretations would be related to a criterion for political indication for the council-member position, in which case many of those appointed are former representatives who have no interest in imposing penalties against leaders in the Legislative Branch or inducing budget cuts in the expenses with personnel in such branches.…”
Section: Figure 3 Limits Of the Expense With Personnel In 2018mentioning
confidence: 95%
“…Lack of uniformization as to how to assess expenses with personnel not only impairs any comparability between balance sheets -especially the Fiscal Management Report -, but it also allows some Courts of Account to increase their own limit to expenses with personnel based on the methodology they apply by avoiding to resort to the adjustment measures set under the LRF. Nunes et al (2019) and Melo et al (2014) identified other divergences in the interpretations of such external control organs, which allow the record of the remaining payable balance over the cash flow available at the end of any tenure (in breach of section 42 of the LRF), or which were permissive with administrations failing to comply with their fiscal targets. The aforementioned authors state as the main justification the political interest of council members in courts who do not wish to harm local legislative or executive branches.…”
Section: Closing Argumentsmentioning
confidence: 99%
“…Os Tribunais de Contas são organizações de auditoria governamental responsáveis pela fiscalização financeira e entrega de serviços governamentais, que tem como principal função de apoio ao Legislativo a emissão de um parecer prévio sobre as contas do Poder Executivo (Speck, 2011;Hidalgo et al, 2016) (Lino & Aquino, 2018;Azevedo & Lino, 2019;Nunes et al, 2019). A literatura prévia traz evidências de diversas más práticas organizacionais nos TCs (Loureiro et al, 2009;Teixeira, 2017).…”
Section: Organização E Processos Nos Tribunais De Contasunclassified
“…A Lei de Responsabilidade Fiscal (LRF), em 2000, aumentou as competências e a importância dos TCs no cenário nacional transformando-os em pilares da gestão fiscal (Loureiro et al, 2009 governamental em estados e municípios de todo país (Puccioni, 2016;Lino & Aquino, 2018;Azevedo & Lino, 2018;Nunes, Marcelino & Silva 2019).…”
Section: Introductionunclassified
See 1 more Smart Citation